Change management in the Indian pharmaceutical industry: a case study. Issue 3 (2017) - Jamwal, Umesh; Panchal, Dilbagh; Kumar, Anish
The aim of this study is to perform qualitative analysis for finding out the best sequence of target practices for a pharmaceutical industry located in the northern part of India. The finding of best sequence of target practices helps in replacing the existing practices and hence improving the business outcome of the particular industry. The analysis has been done using a qualitative approach called matrix of change (MOC). The qualitative information collected from different areas such as organisational system, structure, culture, technology and people have been used for carrying the effective change management in the considered industry. The analysis results were supplied to top management of the considered industry which would be highly useful for the considered industry in the expansion of its business globally.